ANALISA PERBAIKAN SISTEM KERJA SEBAGAI UPAYA MENGURANGI RISIKO MUSCULOSKELETAL DISORDERS MENGGUNAKAN METODE RULA DAN RWL DI CV. KOTAMA SHOES - Uun Novalia Harahap; Yetti Meuthia Hasibuan; Rini Halila Nasution (Jurnal Simetri Rekayasa, 2021)
Health problems in the operator's posture while working have a significant impact on the products produced and indirectly affect the value of work efficiency, uncomfortable workplaces and environments cause company losses, including complaints of musculoskeletal disorders (MSDS). CV KOTAMA SHOES is a company that produces leather shoes, and in the production process, there are still movements and postures that are not ergonomic. This research was conducted to determine the value of risks contained in each work process, starting from the pattern & cutting, assembling, finishing, and storage of parts in the CV. KOTAMA SHOES is based on RULA and RWL scores and will provide proposed improvements to the company to reduce the risk of musculoskeletal disorders. This study uses the Rapid Upper Limb Assessment (RULA) method, a method that is used to analyze the upper body in detail, quickly and the angles formed by working posture, and the Recommended Weight Limit (RWL), a method used to calculate the recommended and recommended load limit for workers to lift under certain conditions. Results of measuring the level of ergonomic risk to complaints of muscle pain (myalgia) in production division workers in CV. KOTAMA SHOES pattern & cutting section gets a rula score of 5 for posture, this assembling gets a score of 7 for posture, finishing gets a score of 5 for posture and storage gets a score of 3 for posture. Based on this score, the posture of the assembling part is at level 4, which is very risky, further treatment needs to change as soon as possible. Improvement recommendations are given to reduce/solve workers' problems with complaints of muscle pain (myalgia) in the production department in CV. KOTAMA SHOES is by changing the movement or working posture in the production of leather shoe processing and the recommended object load for the type of work performed by employees in the assembling section is a maximum of 15.73 kg with a lifting index of 0.082 kg.